2004
DOI: 10.1038/nrg1448
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 21 and Down syndrome: from genomics to pathophysiology

Abstract: The sequence of chromosome 21 was a turning point for the understanding of Down syndrome. Comparative genomics is beginning to identify the functional components of the chromosome and that in turn will set the stage for the functional characterization of the sequences. Animal models combined with genome-wide analytical methods have proved indispensable for unravelling the mysteries of gene dosage imbalance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
501
1
21

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 611 publications
(533 citation statements)
references
References 88 publications
10
501
1
21
Order By: Relevance
“…An expanding number of studies have reported the presence of chronic oxidative stress and mitochondrial dysfunction in DS at both the cellular and organismal levels (Annerén & Epstein, 1987; Busciglio & Yankner, 1995; Antonarakis et al, 2004; Lott & Dierssen, 2012; Campos et al, 2011). Recently, we reported that decreased mitochondrial activity, increased ROS and mitochondrial fragmentation in DS cells are associated with transcriptional activation of the nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) signaling pathway (Helguera et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An expanding number of studies have reported the presence of chronic oxidative stress and mitochondrial dysfunction in DS at both the cellular and organismal levels (Annerén & Epstein, 1987; Busciglio & Yankner, 1995; Antonarakis et al, 2004; Lott & Dierssen, 2012; Campos et al, 2011). Recently, we reported that decreased mitochondrial activity, increased ROS and mitochondrial fragmentation in DS cells are associated with transcriptional activation of the nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) signaling pathway (Helguera et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Down syndrome (DS) occurs due to non-disjunction of chromosome 21 and is the leading genetic cause of mental retardation (MR) [12,27,33]. Other than the presence of an additional chromosome, factors such as allelic variation in candidate genes for MR may al-so contribute to the complex phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…In the vast majority of cases, DS results from the presence of an extra copy of chromosome 21. 1,2 A major goal of understanding the molecular pathology of DS is identifying genotype -phenotype correlations, that is the identification of HSA21 genes or other functional genomic elements that contribute to the specific aspects of the phenotype. There have been several general approaches to this problem: (i) mapping of partial trisomy 21 cases in human, 3 -8 (ii) the construction of partial trisomy mouse models with different orthologous regions of HSA21 9 -11 and (iii) the analysis of gene expression in cells and tissues of DS individuals or mouse models of DS, both of the transcriptome 12 -15 and genes from the aneuploid chromosome.…”
Section: Introductionmentioning
confidence: 99%